Children and Family in Late Antique Egyptian Monasticism - Schroeder, Caroline T. (University of Cambridge ESOL Examinations, 2020)
Cover -- Half-title page -- Title page -- Copyright page -- Dedication -- Contents -- List of Figures -- Acknowledgments -- List of Abbreviations -- Introduction -- Part I Finding Children -- Chapter 1 Documenting the Undocumented: Children in the Earliest Egyptian Monasteries -- Chapter 2 The Language of Childhood -- Part II Representations -- Chapter 3 Homoeroticism, Children, and the Making of Monks -- Chapter 4 Child Sacrifice: From Familial Renunciation to Jephthah's Lost Daughter -- Chapter 5 Monastic Family Values: The Healing of Children -- Part III A Social History -- Chapter 6 Making New Monks: Children's Education, Discipline, and Ascetic Formation -- Chapter 7 Breaking Rules and Telling Tales: Daily Life for Monastic Children -- Chapter 8 The Ties That Bind: Emotional and Social Bonds between Parents and Children -- Conclusion: Monastic Genealogies -- Bibliography -- Index of Ancient Sources -- Index of Names and Subjects.